2010
DOI: 10.1093/nar/gkq618
|View full text |Cite
|
Sign up to set email alerts
|

The Trypanosoma brucei MitoCarta and its regulation and splicing pattern during development

Abstract: It has long been known that trypanosomes regulate mitochondrial biogenesis during the life cycle of the parasite; however, the mitochondrial protein inventory (MitoCarta) and its regulation remain unknown. We present a novel computational method for genome-wide prediction of mitochondrial proteins using a support vector machine-based classifier with ∼90% prediction accuracy. Using this method, we predicted the mitochondrial localization of 468 proteins with high confidence and have experimentally verified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 67 publications
(95 reference statements)
0
54
0
Order By: Relevance
“…Algorithmic prediction programs [Phobius (38) or transmembrane prediction using hidden Markov models predictor (39)] suggested that the translated protein, named "TbCls," contains two C-terminal transmembrane domains and may be targeted to mitochondria (according to MitoCarta predictor) (40). Similar to bacterial-type Cls, TbCls contains two highly conserved H(X)K (X) 4 D motifs found in the active sites of PLD, nucleases, and pox envelope proteins (24).…”
Section: Resultsmentioning
confidence: 99%
“…Algorithmic prediction programs [Phobius (38) or transmembrane prediction using hidden Markov models predictor (39)] suggested that the translated protein, named "TbCls," contains two C-terminal transmembrane domains and may be targeted to mitochondria (according to MitoCarta predictor) (40). Similar to bacterial-type Cls, TbCls contains two highly conserved H(X)K (X) 4 D motifs found in the active sites of PLD, nucleases, and pox envelope proteins (24).…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of the 47.5-kDa protein, all the co-purifying proteins are essential in one or more life stages of the trypanosome (Table 1) based on high-throughput RNAi analysis (Alsford et al 2011). The 17.9-kDa hypothetical protein has a predicted mitochondrial location (Zhang et al 2010), however it was associated consistently with TbE5 and TbG2 in reciprocal purifications. The association of TbE5 in a complex with a protein predicted to have enzymatic activities involved in two of the three steps of mRNA cap formation is a compelling argument for the involvement of TbE5 in mRNA metabolism, and hence the regulation of translation, opening a multitude of new questions.…”
Section: Rna-binding and Cap 0 Maturation Domains Identified In Tbeifmentioning
confidence: 99%
“…KREPB9 had a weaker signal than KREPB10, possibly implying a smaller amount of protein. KREPB9 was previously reported to have mitochondrial localization using a green fluorescent protein (GFP) fusion protein (53). Thus, both KREPB9 and KREPB10 are mitochondrial proteins.…”
Section: Identification Of Krepb9 and Krepb10 Krepb9 And Krepb10mentioning
confidence: 99%